Marine top predators as climate and ecosystem sentinels. Issue 10 (4th November 2019) - Hazen, Elliott L; Abrahms, Briana; Brodie, Stephanie; Carroll, Gemma; Jacox, Michael G; Savoca, Matthew S; Scales, Kylie L; Sydeman, William J; Bograd, Steven J
Abstract : The rapid pace of environmental change in the Anthropocene necessitates the development of a new suite of tools for measuring ecosystem dynamics. Sentinel species can provide insight into ecosystem function, identify hidden risks to human health, and predict future change. As sentinels, marine apex (top) predators offer a unique perspective into ocean processes, given that they can move across ocean basins and amplify trophic information across multiple spatiotemporal scales. Because use of the terms "ecosystem sentinel" and "climate sentinel" has proliferated in the scientific literature, there is a need to identify the properties that make marine predators effective sentinels. We provide a clear definition of the term "sentinel", review the attributes of species identified as sentinels, and describe how a suite of such sentinels could strengthen our understanding and management of marine ecosystems. We contend that the use of marine predators as ecosystem sentinels will enable rapid response and adaptation to ecosystem variability and change.